The effect of exchange rate volatility on international trade and foreign direct investment (FDI) in developing countries along "one belt and one road" - Rashid Latief; Lin Lefen (International Journal of Financial Studies, 2018)
The 'One Belt and One Road' (OBOR) project was started by the Chinese government with the aim of achieving sustainable economic development and increasing cooperation with other countries. This project has five major objectives, which include (i) increasing trade flow, (ii) encouraging policy coordination, (iii) improving connectivity, (iv) obtaining financial integration, and (v) fortifying closeness between people. This paper aims to analyze the effect of exchange rate volatility on international trade and foreign direct investment (FDI) in developing countries along 'One Belt and One Road'. We selected seven developing countries which are part of this project, namely Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka. We collected panel data for the period 1995 to 2016 from the U.S. Heritage Foundation, International Financial Statistics (IFS) (a database developed by the International Monetary Fund), and World Development Indicators (WDI) (a database developed by the World Bank). We applied Generalized Autoregressive Conditional Heteroscedasticity (GARCH) (1,1) and threshold-Generalized Autoregressive Conditional Heteroscedasticity (TGARCH) (1,1) models to measure the exchange rate volatility. Furthermore, we employed a fixed effect model to analyze the relationship of exchange rate volatility with international trade and FDI. The results of this paper revealed that exchange rate volatility affects both international trade and FDI significantly but negatively in OBOR-related countries, which correlates with the economic theory arguing that exchange rate volatility may hurt international trade and FDI. It can be concluded that exchange rate volatility can adversely affect international trade and FDI inflows in OBOR-related countries.
Keywords: C33; F21; F23; 330; exchange rate volatility; international trade; foreign direct investment (FDI); One Belt and One Road (OBOR)